Implementation of Integrated Discovery Learning Model of Generic Science Skills to Improve HOTS - Ani Sutiani; Cinta Bela (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The purpose of this study was to determine the increase in students' high-order thinking skills after the application of the discovery learning model integrated with generic science skills on chemical equilibrium material in class XI of SMA Negeri 5 Tanjung Balai. The sampling technique was carried out using the random sampling technique, namely taking one class randomly by drawing lots. The design of this study was a one group pretest-posttest design. In learning, the test instruments used were cognitive levels C1 to C6, namely multiple choice questions. Through hypothesis testing using one sample T-Test, data significance was obtained < 0.05 so that it can be concluded that Ha is accepted, which means that the average value of students taught with the discovery learning model integrated with generic science skills on chemical equilibrium material reached a minimum of 75.